Sez6 levels are elevated in cerebrospinal fluid of patients with inflammatory pain–associated conditions. (March 2019) - Roitman, Maria; Edgington-Mitchell, Laura E.; Mangum, Jon; Ziogas, James; Adamides, Alexios A.; Myles, Paul; Choo-Bunnett, Hearan; Bunnett, Nigel W.; Gunnersen, Jenny M.
Abstract: Introduction: Seizure-related protein 6 (Sez6) contributes to chronic pain development as sez6 knockout mice show attenuated pain behaviours after peripheral nerve injury, compared with control mice. The type I transmembrane isoform of Sez6 is cleaved by the β-amyloid precursor protein cleavage enzyme 1 (BACE1), resulting in Sez6 extracellular domain shedding from the neuron surface. Objectives: To determine whether this BACE1-shed form of Sez6 can be detected in the cerebrospinal fluid (CSF) and whether Sez6 levels in the CSF are altered in neuropathic pain or chronic inflammatory pain (IP). Methods: We analysed the CSF samples collected during surgery from patients with chronic neuropathic pain (n = 8) or IP (n = 33), comparing them to the CSF samples from patients with suspected subarachnoid haemorrhage that was subsequently excluded (nonsurgical group, n = 5). Western blots were used to determine the relative Sez6 levels in the CSF from the different patient and nonsurgical comparison groups. Results: The results show that BACE1-shed Sez6 can be readily detected in the CSF by Western blot and that the levels of Sez6 are significantly higher in the IP group than in the nonsurgical comparison group. Conclusion: The association between elevated Sez6 levels in the CSF and IP is further evidence for persistent alterations in central nervous system activity in chronic IP conditions. Abstract : Supplemental Digital Content is Available in the Text.